Nanotechnology and construction: use of nanoindentation measurements to predict macroscale elastic properties of high strength cementitious composites - W. R. L. da Silva; J. Němeček; P. Štemberk (Revista IBRACON de Estruturas e Materiais)
This paper aims to present the experimental results involving the use of nanoindentation measurements and prediction of macroscale elastic properties of high performance cementitious composites (HPCC). The elastic properties of HPCC mixture were evaluated at different length scales by nanoindentation (microscale), and elastic moduli and compressive strength tests (macroscale). The nanoindentation results, obtained by grid indentation with subsequent phase deconvolution, were complemented by an independent porosimetry test and inserted into a two-step analytical homogenization scheme to predict the overall macroscale properties. The final results show that the presented method allows a reliable advanced prediction of HPCC elastic properties indicating, thus, that inserting nanotechnology in the concrete industry can be promising, since it would allow the production of a more predictable composite in an easier and less expensive way.